MENGENALKAN LAMBANG BILANGAN MELALUI PERMAINAN MENJATUHKAN SIMBOL ANGKA PADA ANAK USIA DINI - Achmadi achmadi (WAHANA, 2017)
Most early childhood have dificulties for learning numerical. For example, When they are studing,they are tied, boring, and unresponsible about numerical stimulus. So that way they did not havecapabilities to respon about numerical. The child has capabilities to say number one to ten only, buthe does not understand about the number. One of the problems is coused by the teacher and the childhiself. The teacher’s problem is the inappropriate of instruction learning, so the result of learning isnot good enought. While the children’s problems are coused by less of motivated, and less oflearning media that is not increase to student’s motivation. Based on these problems, so theresearcher wants to know to increase of numbers capabilities by using of the number game for earlychildhood. The goals of this reaearch is the falling of symbol number is efective to introduce aboutnumber for early childhood. As indicator of efectiveness are: 1). The children can say numbercorectly and orderedly. 2). The children can ordere the number from small to higher corectley. 3).The children can related among symbol number and the total of material number.4). The children canwrite the symbol of number corectly. This research is a quasi experiment by one group pretes posttestdesign. The collecting data uses performance tes and observation. While the analysis data uses t-statistical. The result of this research has purpose to introduce of the symbol number throught thegame for falling the symbol number.